Concise dictionary of social and cultural anthropology - Morris, Mike [ (Michael Ashley)] (Wiley-Blackwell, 2012)
"The Concise Dictionary of Social and Cultural Anthropology is an accessible, hands-on guide to the hundreds of terms the student of anthropology and the general reader will encounter in dealing with anthropological and ethnographic literature. It includes related terminology from allied fields such as sociology, economics, and geography. The focus is on key concepts in anthropology, with a number of biographies included to identify influential figures who have formulated central theories and conducted the most famous field research within cultures around the world. Extensive bibliographical references provide pointers for further research. Anthropology is a relatively young discipline with a complex history. Anthropological research encompasses hundreds of cultures and provides a valuable perspective on an increasingly globalized world. Written by a researcher and librarian expert in the fields of social and cultural anthropology, this Concise Dictionary offers an invaluable reference to the terminology and accomplishments of this far-reaching and diverse field"--P. [4] of cover.